Creativity and Higher States of Consciousness - Tihoni Brčić (In Medias Res, 2022)
Dream reality and artist-created virtual reality, combined with the reality we perceive as physical, form three realities of human experience. Taking this into account, primary senses seem incomplete without extrasensory senses, which allow access to higher states of consciousness. Artists sometimes use those states as the source of creativity, inspiration, and ideas. The real-time neurofeedback shows brainwave activity in the theta frequency range in a creativity-related Hypnagogic state. Alpha and delta frequencies are also creativity-related. Alpha is observed during the inspiration stage of creative thinking, while theta occurs during transcendental meditation and deep sleep. Neurofeedback is also used to create works of art. Higher states of consciousness-inducing techniques include dream machines, mind machines, binaural beats, hallucinogenic drugs, and most advantageous – float tanks. Holistic methods like meditation, hypnotherapy, and energy healing are also helpful. Meditation seems to be the most effective, with the ability to control lucid dreaming and out-of-body experiences to an extent. The generation of creative ideas is a phenomenon that defies scientific explanation. The author’s experiences in higher states of consciousness in art, meditation, and energy healing, make him confident that higher states of consciousness are legitimate sources of creativity and essential to the overall health of body, mind, and soul.